Refiguring the Real : Picture and Modernity in Word and Image, 1400-1700 - Braider, Christopher, 1950- (Book collections on Project MUSE., 1993)
In a major analysis of pictorial forms from the late Middle Ages to the Enlightenment, Christopher Braider argues that the painted image provides a metaphor and model for all other modes of expression in Western culture-particularly literature, philosophy, religion, and science. Because critics have conventionally explained visual images in terms of verbal texts (Scripture, heroic poetry, and myth), they have undervalued the impact of the pictorial naturalism practiced by painters from the fifteenth century onward and the fundamentally new conception of reality it conveys. By reinterpreting m.